Postępowanie we wrodzonej niedrożności przewodu nosowo-łzowego – wytyczne Polskiego Towarzystwa Okulistycznego - Urban, Beata; Samsel, Agnieszka; Filipek, Erita; Niwald, Anna Maria; Krzyżanowska-Berkowska, Patrycja; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2020)
Authors present the etiology, clinical presentation, diagnosis, and management of congenital nasolacrimal duct obstruction (CNLDO). The problem of immediate and deferred probing for CNLDO is discussed. The paper presents also guidelines of the Polish Ophthalmological Society in CNLDO management.